Biliary Stent Migration Causing Simultaneous Duodenal and Distal Ileal Perforation: A Rare Complication - Perisamy, Rajeev Shamsuddin (IIUM Medical Journal Malaysia, 2020)
Introduction: Endoscopic retrograde cholangiogram pancreatography (ERCP) and biliary stenting is a minimally invasive procedure widely utilised to relieve biliary obstruction. Although not common, it is related with several possible complications. Stent migration causing duodenal perforation is 1 of its rare complications as being described in several previous case reports. However up to date there is no case report on migrated stent with subsequent duodenal and distal ileal perforation as will be discussed here. Importance of radiological examinations and its related findings in diagnosing this very rare complication will be described in this article.